Deregulation and Firm Investment : Evidence from the Dismantling of the License System in India - Kandilov, Ivan T. (Taylor and Francis, 2017)
We analyse the impact of deregulatory reforms in India during the 1990s, which eliminated compulsory industrial licensing, on manufacturing firms’ investment decisions. We find an economically and statistically significant positive effect of delicensing on investment. We also show that firms in states with better credit conditions benefitted more from the removal of licences. Moreover, our analysis demonstrates that the increase in investment was predominantly driven by smaller firms.